THE ACTIVE ROLE OF THE FAMILY ON BUILDING THE STUDENTS’ CHARACTERS AT UNIVERSITAS KRISTEN INDONESIA - Tyas, E. Handayani (International Journal of Research -GRANTHAALAYAH, 2020)
This research is aimed at describing whether parents have an active role in building the character of students and find reasons why it is so. It was done at Universitas Kristen Indonesia, and the respondents were students of Christian Religious Education Department exactly in the second semester. The research method used was the mix method research. The instruments used were the sheet which were analyzed by looking for percentages of all questionnaires (quantitatively) and the interview quidance which were analyzed descriptively (quantitatively). The findings of the research obtained are: a) 18% of all parents of students who always play a role in building the students character; b) 27% of all people parents of students who often play a role in building the students character; c) 36% of all parents of students who sometimes play a role in building the students character, and d) 19% of all parents of students who does not play a role in building the students character. So, it is concluded that most of the parents play an inactive role in building the students character. As it is expected by the completion of this research is that in building the students’ character, the role of parents is needed. For this reason, the role of parents needs to be improved and also the cooperation between parents, campus spiritual institutions, and also lecturers need to be held and improved to build the character of the students.